Circular Wilson loops in defect conformal field theory - Aguilera Damia, Jeremías (2017)
We study a D3-D5 system dual to a conformal field theory with a codimension-one defect that separates regions where the ranks of the gauge groups differ by k. With the help of this additional parameter, as observed by Nagasaki, Tanida and Yamaguchi, one can define a double scaling limit in which the quantum corrections are organized in powers of λ/k2, which should allow to extrapolate results between weak and strong coupling regimes. In particular we consider a radius R circular Wilson loop placed at a distance L, whose internal space orientation is given by an angle χ. We compute its vacuum expectation value and show that, in the double scaling limit and for small χ and small L/R, weak coupling results can be extrapolated to the strong coupling limit.